If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5m + 15 = 4(8 + -1m) Reorder the terms: 15 + -5m = 4(8 + -1m) 15 + -5m = (8 * 4 + -1m * 4) 15 + -5m = (32 + -4m) Solving 15 + -5m = 32 + -4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '4m' to each side of the equation. 15 + -5m + 4m = 32 + -4m + 4m Combine like terms: -5m + 4m = -1m 15 + -1m = 32 + -4m + 4m Combine like terms: -4m + 4m = 0 15 + -1m = 32 + 0 15 + -1m = 32 Add '-15' to each side of the equation. 15 + -15 + -1m = 32 + -15 Combine like terms: 15 + -15 = 0 0 + -1m = 32 + -15 -1m = 32 + -15 Combine like terms: 32 + -15 = 17 -1m = 17 Divide each side by '-1'. m = -17 Simplifying m = -17
| 5*x+3*y=10 | | (4x+2y)=324 | | 91-y=81-0.5y | | 5b^3*3b^5= | | 4(2m-5)=3(2m+8) | | 4x+2y=324 | | 1x+1y=91 | | x(2x+11)=12 | | (X+2)(x-2)=5(x+4) | | 2x-4(x-3)=15 | | 4x^2-52x+153=0 | | 9y-2y=5(y-4) | | 3x^2*(x^2-1)-x^3*2x=0 | | 2u^2-7u+3=2 | | 7x+5=3x+18 | | x=156+0.6x | | x(2x^2-32)=0 | | 100-8y=60 | | 3a-6=a-4 | | 6logx+2=0 | | z^6=27 | | 3=1+0.5v | | 2r+9=r+15 | | z^2+16+30i=0 | | 0.05(500)+40=0.07(500)+30 | | x^3=0.75 | | f(x)=x^3+13x^2+36x | | x^3+6x^2+11x-6=0 | | 0.05x+40=0.07x+30 | | 2u^2-7u-11=0 | | -80-12.2= | | 36=x-50 |